2016
DOI: 10.1213/ane.0000000000001205
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lidocaine on Central Respiratory Neuron Activity and Nociceptive-Related Responses in the Brainstem–Spinal Cord Preparation of the Newborn Rat

Abstract: Our findings indicate that lidocaine depressed nociception-related responses at lower concentrations than those that induced respiratory depression. Our report provides the basic neuronal mechanisms to support the clinical use of lidocaine, which shows antinociceptive effects with minimal side effects on breathing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Some studies have found that high doses of lidocaine and its quaternary derivatives induce respiratory depression and the underlying mechanisms have been investigated. High doses of lidocaine (100–400 μM) decrease the C4 burst rate, eventually resulting in the complete cessation of respiratory rhythm, and decrease the burst duration and negative slope conductance of preinspiratory neurons (Shakuo et al, 2016). Takahashi et al (2016) reported that QX‐314 also decreases the C4 burst rate, amplitude, and slope during the initial rising phase and the action potentials of respiratory neurons with a half‐decay time of about 5 min.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that high doses of lidocaine and its quaternary derivatives induce respiratory depression and the underlying mechanisms have been investigated. High doses of lidocaine (100–400 μM) decrease the C4 burst rate, eventually resulting in the complete cessation of respiratory rhythm, and decrease the burst duration and negative slope conductance of preinspiratory neurons (Shakuo et al, 2016). Takahashi et al (2016) reported that QX‐314 also decreases the C4 burst rate, amplitude, and slope during the initial rising phase and the action potentials of respiratory neurons with a half‐decay time of about 5 min.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine and morphine inhibited slow ventral root potentials following ipsilateral dorsal root stimulation in newborn rat spinal cord preparation in vitro [10]. We recently reported that lidocaine depressed nociception-related responses at lower concentrations than those that induced respiratory depression [11]. However, there is no report regarding the effects of QX-314 and combined application of capsaicin on nociception-related responses in the above in vitro experimental model.…”
Section: Introductionmentioning
confidence: 96%